(untitled) (Research, Society and Development, 2022)
Objective: To analyze in the scientific literature the published evidence on the suffering of the medical professional in the face of the patient’s death. Method: An integrative review of the scientific literature published in Pubmed, Scielo, Lilacs, Cinahl, Scopus and Web of Science databases was performed. The search was guided by the research question: What are the scientific evidence about the physician’s suffering in the face of the inpatient’s death? The search was carried out in June and July 2022. Scientific articles published between the years 2017 to 2022 were included. Results: Seven articles with varied methodological designs were selected, reporting the physician’s feeling regarding the patient’s death, its consequences and coping mechanisms. Conclusion: The physician’s suffering in the face of the patient’s death is present with varied consequences and greater training of this professional is necessary, as well as further studies are needed to evaluate the various aspects and coping mechanisms.